Pengembangan Perangkat Pembelajaran Berbasis Inkuiri Terbimbing untuk Meningkatkan Kemandirian Belajar dan Hasil Belajar Peserta Didik pada Materi Asam Basa - Yunus, Irda Sani; Sudding, Sudding; Herawati, Netti (Program Pasca Sarjana UNM, 2023)
This development research aims at developing and producing a valid, practical, and effective guided inquiry-based learning device to increase independent learning and learning outcomes. The development model used was the 4D development model. Theh results of the study are (1) the device development process consisted of 4 stages, namely the defining stage, design stage, development stage, and dissemination stage, (2) the learning device meets a very valid category. The learning device is practical because at the practical test which related to (a) the implementation of guided inquiry-based learning device achieves the mean score M=1.88 with the category of implemented completely, (b) the teacher and students’ responses are positive with 92.94% and 89.11% with the category of very practical. The guided inquiry-based learning device is effective because it has met effective criteria with the following results: (a) the increase of independent learning of students before learning is 56.88% and after learning is 82.28% with independent category, (b) the completeness of learning outcomes meets the effective criteria with 85.71%.